SUCCESS FACTOR ANALYSIS IMPLEMENTATION OF GOVERNMENT INTERNAL CONTROL SYSTEM (SPIP) POLICY IN CENTRAL JAVA PROVINCE GOVERNMENT FROM GRINDLE PERSPECTIVE - Prayudo, Edo Setya; Rozikin, Mochammad; Anggraeni, Niken Lastiti Veri (Erudio Journal of Educational Innovation, 2025)
The reason of composing this diary is to supply an illustration of the victory of neighborhood government from Mary S. Grindle's point of view in executing arrangement, specifically Government Direction Number 60 of 2008 concerning the Government Inside Control Framework (SPIP). This investigate takes a case think about of the Central Java Common Government. The method utilized may be a clear subjective strategy. The comes about of the investigation of the victory variables for actualizing this arrangement are the substance of the approach that help make strides organizational execution. The point of this usage is to realize organizational objectives through compelling and productive exercises, unwavering quality of monetary announcing, security of state resources, and compliance with statutory directions and back from the environment where the usage is actualized counting commitment from administration and bolster from outside organizations.